2023
DOI: 10.2807/1560-7917.es.2023.28.2.2200123
|View full text |Cite|
|
Sign up to set email alerts
|

Countrywide multi-serotype outbreak of Salmonella Bovismorbificans ST142 and monophasic Salmonella Typhimurium ST34 associated with dried pork sausages in France, September 2020* to January 2021

Abstract: The French National Reference Centre for Escherichia coli, Shigella and Salmonella (FNRC-ESS) detected two human clusters of 33 cases (median age: 10 years; 17 females) infected by Salmonella enterica serotype Bovismorbificans, ST142, HC5_243255 (EnteroBase HierCC‑cgMLST scheme) in September–November 2020 and of 11 cases (median age: 11 years; seven males) infected by S. enterica serotype 4,12:i:-, ST34, HC5_198125 in October–December 2020. Epidemiological investigations conducted by Santé publique France link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Derby isolates was highly resolutive and closely related clusters were identified within ST40 and ST71 and genotypes with matrix or geographic persistence were shown. WGS approach has also been used for trace-back microbial investigations, which have indicated DFS as the main source of Salmonella outbreaks 38 , 39 . In our study, cluster 5M (15 cgSNPs) revealed seven 1 ,4,[5],12:i:- isolates from DFS related with an outbreak in 2018 and from pig carcass in 2019, which emphasizes the importance of following good manufacturing practices and validating the DFS production process 40 together with adequate sampling plans and monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Derby isolates was highly resolutive and closely related clusters were identified within ST40 and ST71 and genotypes with matrix or geographic persistence were shown. WGS approach has also been used for trace-back microbial investigations, which have indicated DFS as the main source of Salmonella outbreaks 38 , 39 . In our study, cluster 5M (15 cgSNPs) revealed seven 1 ,4,[5],12:i:- isolates from DFS related with an outbreak in 2018 and from pig carcass in 2019, which emphasizes the importance of following good manufacturing practices and validating the DFS production process 40 together with adequate sampling plans and monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Whole genome sequence data of 173 Salmonella enterica originating from pork and different stages of the DFS production chain in the northeast area of Spain and France were analysed. The sources of the strains were pig carcass (49), pork (38), fresh sausage (16) and pork DFS (70) (Table 1). A total of 125 isolates were collected during Salmonella surveillance, 31 in the context of outbreaks (27 specifically isolated from DFS), 14 and 3 were from IRTA and ANSES culture collections, respectively (Supplementary Table S1).…”
Section: Genome Panel Characteristicsmentioning
confidence: 99%
“…For instance, relevant international health agencies were informed of outbreaks of Salmonella Bovismorbificans ST142 and monophasic Salmonella Typhimurium ST34 in part through the online portal [82]. These forms of instant communication have been noted to facilitate development of risk management strategies [83].…”
Section: Analysing and Sharing Datamentioning
confidence: 99%
“…Many outbreaks due to the MVST have been reported to date in Europe and in the United States, and most of them have been linked to RTE food products. For example, two outbreaks were linked to the consumption of salami and pork products in 2009 [15] and 2010 [16], respectively, in North Italy; three different outbreaks were linked to the same product, dried pork sausage, in France [17,18] and in Spain [19] in 2011 and again in France in 2020 [20]; one outbreak was associated with roast pork in Spain in 2016 [21]; and a multi-state outbreak was linked to pork products in Washington State in 2015 [22].…”
Section: Introductionmentioning
confidence: 99%